Effectiveness of interest rate policy of the Fed in management of subprime mortgage crisis - Samet Gunay; Bojan Georgievski (Journal of Risk and Financial Management, 2018)
The federal funds rate is one of the most important monetary policy instruments of Federal Reserve Bank of America. In this study, we analyze the effectiveness of Fed interest rate policy on different markets in the period between 1976 and 2016 through Markov regime-switching regression analysis. Results indicate that Federal funds' rate affects labor and housing markets with a few months' lag. However, the influence of Federal funds rate on inflation rate is quite limited. It is most probable that Fed employs alternative monetary instruments to regulate inflation. The most interesting results are obtained in the domain of personal savings. The interaction of personal savings and Federal funds rate is significant during both expansion and recession regimes.
Keywords: 330; subprime mortgage crisis; Fed; interest rate policy